Natural occurrence and pathogenicity of Xanthomonas bacteria on selected plants - Chala, A.; Kebede, T.; Blomme, Guy (Academic Journals, 2016)
The bacterial genus Xanthomonas consists of several species of economic importance, among which Xanthomonas campestris pv.musacearum (Xcm), the cause of enset and banana wilt is the most important in tropical Africa.However, the natural occurrence and host range of this species is yet to be clarified.The objectives of this study were to verify the presence of Xanthomonas bacteria on plants growing in and around enset gardens in South and Southwest Ethiopia, and to elucidate the pathogenicity of Xcm strains to cultivated and wild plants.Several economical and ornamental plants were assessed for wilting in South and Southwest Ethiopia.Wilting was visible on Canna spp. with 9.8% incidence and 30% prevalence, while reddish streak symptoms (typical of Xanthomonas bacteria) were observed on the leaves of sugarcane, sorghum and wild sorghum with disease incidence ranging from 20 to 80%, and prevalence varying from 30 to 100%.The pathogenicity of three Xcm isolates to five plant species was tested in a factorial experiment arranged in CRD with five replications.All the tested Xcm isolates were found to be pathogenic to banana, cultivated and wild enset, Canna indica, Canna orchoides, maize, sorghum and finger millet.The analysis of variance for incubation period and disease incidence revealed significant differences (p<0.05)among test plants and isolates.Results suggest marked variations among test plants' ability to resist the bacterium.Variations were also evident in the aggressiveness of the bacterial isolates.On the other hand, enset and banana did not show any symptom after being inoculated with four Xanthomonas isolates from other crops.